Mysticism, evil, and Cleanthes’ dilemma - Lorkowski, C. M. (International journal of philosophy and theology, 2015)
Hume’s Dialogues give one of the most elegant presentations of the Problem of Evil ever written. But often overlooked is that Hume’s problematic takes the form of a dilemma, with the traditional Problem representing only one horn. The other is what Hume calls ‘mysticism,’ a position that avoids the Problem of Evil by maintaining that God is wholly other, and that God is therefore good in a fashion that mere humans simply cannot fathom. Mysticism is not the denial of God’s moral perfection defended by Philo’s positing of an indifferent deity. Nor is it an ad hoc final theistic entrenchment meant to stave off the Problem of Evil at any cost. Mysticism is, in fact, a position that Hume takes quite seriously and helped shape theism as it was practiced in Hume’s day. This paper studies Hume’s relationship with mysticism. First, it will recast the Problem of Evil as Hume intended, as only part of the larger theistic dilemma of choosing between anthropomorphism and mysticism. Once this polarization is understood and the respective consequences of adopting either of the two opposites is traced out, I locate Hume’s ‘genuine theism’ as significantly lying between these two extremes.